ENVIRONMENTAL UNCERTAINTY, MANAGERIAL ABILITY AND TAX AGGRESSIVENESS - Syarendra, Jessica Dhea; Kristanto, Ari Budi (Politeknik Negeri Madiun, 2020)
This research aims to examine the effect of environmental uncertainty on tax aggressiveness. Moreover, this research also examines the effect of managerial ability, as a moderating variable, in the relationship between environmental uncertainty and tax aggressiveness. This research is useful to the government in identifying the taxpayer?s aggressiveness, particularly in an uncertain business environment. This research uses secondary data obtained from the annual report of 92 manufacturing companies as a sample. The hypothesis testing is done using Moderated Regression Analysis (MRA). The variables used in this study are environmental uncertainty (as the independent variable), tax aggressiveness (dependent variable) and managerial ability (moderating variable). This study is found that there is a positive relationship between environmental uncertainty towards tax aggressiveness. Moreover, this study also found that managerial ability roles can influence the relationship between environmental uncertainty and tax aggressiveness. The existence of managerial ability can weaken the relationship of environmental uncertainty on tax aggressiveness.